Pengaruh Pemberian Pupuk Mikro Zn dan Cu serta Pupuk Tanah terhadap Perkembangan Empoasca sp. pada Areal Tanaman Teh - Fani Fauziah; Restu Wulansari; Erdiansyah Rezamela (Agrikultura, 2018)
ABSTRACTThe effect of Zn and Cu micro-fertilizer and soil fertilizer on the development of Empoasca sp. in tea plantation areaFertilization has an important role for the entire process of metabolism and improves plant health. Tea plants are plants that require macro and micro nutrient inputs. The micro elements of Zn and Cu are needed for energy production, protein synthesis, formation of auxin hormones and increament of plant resistance to pest attack. This study aimed to determine the effect of Zn and Cu micro fertilizer and soil fertilizer on the development of Empoasca sp. The study was conducted from January to July 2017 at Gambung Experimental Station with an altitude of 1350 asl. The experiment was designed with Randomized Block Design (RBD) Factorial pattern with the following treatment arrangement: Factor A = 1) Without Micro Fertilizer, 2) Micro Fertilizer of Zn and Cu 200 g/ha/application, and 3) Zn and Cu 300 g/ha/application; Factor B = 1) Soil fertilizer of 100% recommended dosage, 2) Soil fertilizer of 75% recommended dosage, and 3) Soil fertilizer of 50% recommended dosage. All treatmnets were repeated three times. Application of micro fertilizers was carried out after six times of tea-leaf picking, while soil fertilizer was applied once at the beginning of the experiment. Observation parameters were population and attack intensity of Empoasca sp., as well as shoot production (kg/25 m2 plot size). The results showed that the application of fertilizers had an effect on the decrease of attack intensity and the population of Empoasca sp. in all treatments. Average attack intensity and population of Empoasca sp. at the end of the observation did not differ significantly of 31.64% and 2.55 Empoasca sp. per plant. Meanwhile, the highest total production of 36.56 kg/plot was obtained from the application of micro fertilizer Zn and Cu in the dosage of 200 g/ha/application at all doses of soil fertilizer, but there was no interaction between treatment factors.Keywords: Micro fertilizer, Soil fertilizer, Empoasca sp., Tea plantABSTRAKPemupukan memegang peranan penting untuk seluruh proses metabolisme dan meningkatkan kesehatan tanaman. Tanaman teh merupakan tanaman yang memerlukan input unsur hara makro dan mikro. Unsur mikro Zn dan Cu diperlukan tanaman untuk produksi energi, sintesis protein, pembentukan hormon auksin serta meningkatkan resistensi terhadap serangan organisme pangganggu tanaman. Penelitian ini bertujuan untuk mengetahui dampak pemberian pupuk mikro Zn dan Cu serta pupuk tanah terhadap perkembangan Empoasca sp. Penelitian dilaksanakan dari bulan Januari hingga Juli 2017 di Kebun Percobaan Gambung dengan ketinggian 1.350 mdpl. Percobaan dirancang dengan Rancangan Acak Kelompok (RAK) pola Faktorial dengan susunan perlakuan sebagai berikut: Faktor A = 1) Tanpa Pupuk mikro, 2) Pupuk mikro Zn dan Cu 200 g/ha/aplikasi, dan 3) Pupuk mikro Zn dan Cu 300 g/ha/aplikasi; Faktor B = 1) Pupuk tanah 100% dosis anjuran, 2) Pupuk tanah 75% dosis anjuran, dan 3) Pupuk tanah 50% dosis anjuran. Perlakuan diulang sebanyak tiga kali ulangan. Aplikasi pupuk mikro dilaksanakan setelah pemetikan sebanyak enam kali, sedangkan pemberian pupuk tanah dilakukan satu kali diawal percobaan. Parameter pengamatan yaitu populasi, intensitas serangan Empoasca sp., dan produksi pucuk (kg/plot 25 m2). Hasil penelitian menunjukkan bahwa pemberian pupuk berpengaruh terhadap penurunan intensitas serangan dan populasi Empoasca sp. pada seluruh perlakuan. Rata-rata intensitas serangan dan populasi Empoasca sp. pada akhir pengamatan tidak berbeda nyata sebesar 31,64% dan 2,55 ekor per tanaman. Sementara itu, total produksi tertinggi diperoleh dari aplikasi pupuk mikro Zn dan Cu dosis 200 g/ha/aplikasi pada semua dosis pupuk tanah yaitu sebesar 36,56 kg/plot, namun tidak terjadi interaksi antar faktor perlakuan.Kata Kunci: Pupuk mikro, Pupuk tanah, Empoasca sp., Tanaman teh